The Influence of Motivation and Work Discipline on Employee Performance at PT. PLN ULP Sampit - Ivan Fathurois Azis; Saladin Ghalib; M. Hasanur Arifin; Irwansyah (Magister Administrasi Bisnis ULM, 2025)
Abstract: This research aims to examine the influence of motivation and work discipline on employee performance at PT PLN ULP Sampit both partially and simultaneously. The research approach used is a quantitative approach, with a sample of 52 respondents selected using saturated sampling techniques. Data collection was conducted using a questionnaire, and the data analysis results were obtained using multiple linear regression. The research findings indicate that motivation has a significant partial effect on employee performance, work discipline has a significant partial effect on employee performance, and both motivation and work discipline have a significant simultaneous effect on employee performance